Impact Assessment of Non-Technological Fluid Accumulations in the Cavity of an Existing Gas Pipeline on the Energy Efficiency of Its Operation - Rybitskyi, I.V.; Oliynyk, A.P.; Yavorskyi, A.V.; Karpash, M.O.; Tsykh, V.S.; Slobodyan, M.B. (Physics and Chemistry of Solid State, 2019)
The given methodology for assessing the efficiency coefficient of a gas pipeline based on the determination of a new informative parameter - the maximum level of non-technological fluid accumulations in its cavity. The proposed methodological approaches make it possible to respond faster regarding the removal of critical volumes of accumulated fluid from the gas pipeline cavity in order to maintain its energy and operational efficiency at the proper level.